2004
DOI: 10.1128/aac.48.10.4047-4049.2004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Phenotypic and Genotypic Florfenicol Resistance in Escherichia coli

Abstract: This study evaluated the relationship between florfenicol resistance and flo genotypes in 1,987 Escherichia coli isolates from cattle. The flo gene was detected in 164 isolates, all of which expressed resistance to florfenicol at MICs of >256 g/ml. The florfenicol MICs for all isolates that lacked flo were <16 g/ml.Florfenicol is a fluorinated analog of chloramphenicol approved by the Food and Drug Administration in 1996 for the treatment of bovine respiratory disease (BRD) pathogens. The main florfenicol targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…We hypothesize that this is due to selection of E. coli with a plasmid or chromosomally located flo gene conferring resistance to florfenicol and chloramphenicol [27,33]. Additionally, florfenicol treatment selected for E. coli isolates that exhibited simultaneous resistance to several other antimicrobial classes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that this is due to selection of E. coli with a plasmid or chromosomally located flo gene conferring resistance to florfenicol and chloramphenicol [27,33]. Additionally, florfenicol treatment selected for E. coli isolates that exhibited simultaneous resistance to several other antimicrobial classes.…”
Section: Discussionmentioning
confidence: 99%
“…Florfenicol is a bacteriostatic antimicrobial with similar mode of action to chloramphenicol, binding to the 50S subunit of bacterial ribosomes. The flo gene confers resistance to chloramphenicol and florfenicol, and is most commonly located on a large transferable plasmid in bovine enteric E. coli [27,33].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, detection of flo in a sample can indicate whether colonies are likely to be florfenicol resistant. 37 In large epidemiologic studies, many samples are evaluated for the presence of resistant organisms. In addition to screening many different bacteria for specific resistances, community DNA approaches could quickly indicate whether specific resistance genes are present within any of the bacteria in the community of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…However florfenicol resistance has been documented in E. coli of animal origin (Singer et al, 2004) and it has been shown that floR genetic determinants and others (i.e. cmlA, cat1, cat2) were also largely related to florfenicol resistance (Li et al, 2007).…”
Section: Nomentioning
confidence: 99%